Study of the Validity of Student Academic Achievement Instruments (CLEI) - Siti Sugih Hartiningsih; Yeni Mahwati; Ejeb Ruhyat; Gugum Pamungkas; Meta Dwi Tamara; Maya Indriati; Berty Risyanti (Postgraduate, University of Mataram, 2025)
This study aims to study of the validity of student academic achievement instruments (CLEI). This research is quantitative descriptive. The population in the study is a subject who meets the criteria that have been set, namely all students of the class of 2021 semester 2 at STIKes Dharma Husada who have joined the whatsapp group, namely 129 students. Data analysis in this study uses univariate analysis, namely by calculating the frequency distribution of each characteristic measured, then conducting bivariate analysis in the form of a grain validity test using the Pearson product moment correlation formula and multivariate analysis in the form of a construct validity test using a factor analysis test. As many as 93% of the questions were declared valid with a reliability value of 0.917, factors formed from the component of academic potential as many as 5 factors, time management 2 factors, academic stress management 1 factor and the component of involvement in campus activities 2 factors